The reliability and validity for Japanese type 2 diabetes patients of the Japanese version of the acceptance and action diabetes questionnaire - Junichi Saito; Wataru Shoji; Hiroaki Kumano (BioPsychoSocial Medicine, 2018)
Abstract Background The purpose of this study was to determing which psychological traits of Japanese type 2 diabetes patients would provide reliability and validity to the Japanese version of the Acceptance and Action Diabetes Questionnaire (AADQ-J). Methods Various questionnaires were administered to type 2 diabetes patients who were registered on the database of the research service provider; data from a total of 600 patients (mean ± SD age was 57.50 ± 9.87 years, female 21.83%) were analyzed. Results Three items were excluded because of psychometric concerns related to the original 11-item AADQ. Confirmation factor analyses revealed that the eight-item version demonstrated the best indicators of a goodness of fit. The questionnaire showed adequate internal consistency. The questionnaire demonstrated high measurement accuracy in broad trait values by the test information function of Item Response Theory. The questionnaire showed stronger positive correlations with self-care activities and HbA1c than with diabetes distress and depressive mood. Conclusions The eight-item Japanese version of AADQ has reliability and validity for type 2 diabetes patients.